Pengaruh Kepuasan Kerja Dan Pengembangan Karir Terhadap Retensi Karyawan Pada Hotel Prime Plaza Kualanamu - Malau, Vivy Anggi; Hutahaean, Theresia; Syahrul, Syahrul (Politeknik Pariwisata Medan, 2023)
The goal of this study is to see how (1) work satisfaction affects employee retention and (2) career development affects employee retention at Hotel Prime Plaza Kualanamu. This study takes a quantitative method. The population and sample are comprised of 42 employees from Hotel Prime Plaza Kualanamu, drawn using a saturation sampling technique. Job satisfaction (X1) and career development (X2) are the independent variables, whereas employee retention (Y) is the dependent variable. Simple linear regression analysis and multiple linear regression analysis are used to analyse the data, which is processed using the IBM SPSS Statistics 25 test tool. This study found that (1) work satisfaction has a favourable and significant effect on employee retention. This is supported by the t test findings, which show that work satisfaction variables are Thitung 3.360 > Ttabel 2.203 and sig = 0.000 0.050. (2) Career development has a large and favourable impact on employee retention. This is supported by the t test findings, which show that work satisfaction variables are Thitung 6.220 > Ttabel 2.203 and sig = 0.000 0.050.